Measuring Auditory Discrimination Thresholds in Preschool Children: An Empirically Based Analysis. Issue 3 (2nd October 2018) - Gillen, Nicola; Agus, Trevor; Fosker, Tim
ABSTRACT: Auditory discrimination is an important perceptual skill that seems to develop substantially during early childhood and is predictive of key developmental outcomes like language ability. However, the estimation of reliable auditory discrimination thresholds is impeded by non-sensory limitations in young children that impact task performance. Here we used computerized simulations of child-like and adult-like performance, as well as novel behavioral task modifications with 3- and 4-year old preschool children and adults, to investigate key parameters in the successful estimation of auditory discrimination thresholds in preschool-aged children. The results indicated the most suitable adaptive procedure that is not widely used with young children (75% weighted 1-up 1-down procedure), an appropriate number of trials (20) and step size (relatively small). In addition, using a novel manipulation of level of physical engagement, it was found that threshold estimates are more reliable when children were given a task that involved greater physical engagement (i.e., 3D objects, rather than 2D images on a screen). The overall results provide recommendations for designing procedures to estimate thresholds in preschool or developmentally delayed children.